Stigma towards psychosis: Cross‐cultural differences in prejudice, stereotypes, and discrimination in White British and South Asians. (5th September 2019) - Ahmed, Sehar; Birtel, Michèle D.; Pyle, Melissa; Morrison, Anthony P.
Abstract: Public stigma towards people with mental health problems has been demonstrated in Western societies. Little is known about non‐Western cultures and whether cultures differ in their perceptions of people with mental health problems. Aim of this study was to examine cultural differences in prejudice, stereotypes, and discrimination towards people with psychosis. Participants were from White British and South Asian backgrounds ( N = 128, aged 16–20 years) recruited from two schools and colleges in the United Kingdom. They completed a cross‐sectional survey on affective, cognitive, and behavioural dimensions of stigma. Results revealed significant cultural differences on all three stigma dimensions. South Asians attributed higher anger (prejudice) and dangerousness (stereotypes) to people with psychosis than White British. They also reported lower willingness to help, greater avoidance, and higher endorsement of segregation (discrimination). The effects of ethnic group on helping intentions, avoidance, and segregation endorsement were mediated by anger and by dangerousness. Understanding cultural differences in stigma towards psychosis will be important for designing stigma interventions as well as treatments for people with different cultural backgrounds.